Quality of Life and Its Determinants among Patients on Vitamin K Antagonist Therapy in India: A Baseline Cross- Sectional Analysis - Janet Prameela Dsouza; Jyothi Chakrabarty; Padmakumar Ramachandran; Baby S Nayak; Elsa Sanatombi Devi; Vasudeva Guddattu; Judith Angelitta Noronha Noronha (National Journal of Community Medicine, 2026)
Background: Vitamin K Antagonist (VKA) therapy has been extensively recommended for years to prevent thromboembolic disorders. The continued use of this treatment emphasizes its clinical importance across healthcare settings, particularly in resource-limited countries such as India. Chronic use of this therapy can impact patients’ QOL owing to treatment-related burden. Given that limited data are available related to the QOL of patients on VKA therapy at tertiary referral hospitals in the region, this study was undertaken. Methodology: This study is a cross-sectional analysis of baseline data obtained from a randomized controlled trial. These data were gathered using the QOL tool among 320 patients on VKA therapy. Results: The mean overall quality of life score was 14 ± 1.26. The highest mean scores were recorded in the social, economic, and family domains, whereas the lowest mean scores were noted in the psychological, spiritual, and health functioning domains. College/university education (β = 0.50, 95% CI: 0.10-0.90; p = 0.015) and the absence of comorbidities (β = 0.40, 95% CI: 0.11-0.69; p = 0.007) were significantly associated with better QoL. Conclusions: The findings from this single-center, cross-sectional analysis highlight the significance of considering comorbidities and education when evaluating patients on VKA therapy.